Utilization of Rice-Washing Water as Liquid Organic Fertilizer (LOF) in Sidomekar Village, Katibung Subdistrict, South Lampung Regency - Marpaung, Teli Hosana; Ramadhani, Akbar; Safitri, Tiara; Setyaki, Omar Liandro Aryo; Mufidah, Rintan Roro; Utami, Raden Ayu; Amjahmudin, Ibnu (Indonesian Journal of Community Services Cel, 2025)
This community services activity aims to increase the knowledge and understanding of the community in Sidomekar Village, Katibung Subdistrict, South Lampung Regency regarding the utilization of rice-washing water as liquid organic fertilizer (LOF). This activity took place at Sidomekar Village Hall, Katibung Subdistrict, South Lampung Regency on February 2025 by involving 25 women of Family Welfare Empowerment (PKK) in this village as participants. The methods comprised tool and material preparation, material presentation, training (hands-on practice) of LOF production using rice-washing water, and evaluation via question-and-answer (Q&A) method between the community services team and participants. The evaluation results show that the community of Sidomekar Village, particularly the women of PKK, showed high enthusiasm and curiosity in participating in the material presentation and training sessions, revealed by their attendance rate of 100% and active participation during the discussion. The evaluation results also reveal that they showed high practice’s success and knowledge improvement throughout this activity.